Long-term transformations of the Karkonosze towns - on the example of Karpacz = Przekształcenia zabudowy miejscowości karkonoskich w długim przedziale czasowym - na przykładzie Karpacza - Trocka-Leszczyńska, Elżbieta; Bocheński, Stanisław; Piskozub, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Karkonosze Mountains localities have a long and rich history. Earlier the building development was unique atmosphere and character. We are most interested in contemporary design at the present time. Intensive construction activity is conducted hastily and ill-conceived in the last two decades. The results of this action are visible both in the perception of space and the shaping of technical infrastructure.
Keywords: architektura regionalna; obszary górskie; projektowanie; Karta Sudecka; Karpacz; Karkonosze; regional architecture; designing on highlands; The Charter of Sudetes